2017
DOI: 10.1080/10926771.2017.1350773
|View full text |Cite
|
Sign up to set email alerts
|

Child Abuse—Suicide Resilience Link in African American Women: Interpersonal Psychological Mediators

Abstract: The interpersonal-psychological theory of suicidal behavior (IPTS) is an exemplary model for understanding the desire for suicidal behavior. As such, it is important to explore its applicability in ethnoracial minority groups at increasing risk for suicidal behavior, such as low-income African American women. Guided by the IPTS, the current study used five parallel mediation models to examine if there are links between individual types of childhood abuse (physical, sexual, emotional) and suicide resilience and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 54 publications
3
18
0
2
Order By: Relevance
“…Most frequently investigated (Norman et al, 2012) and relevant for the analyses presented here are sexual, physical, and emotional abuse. Especially sexual and physical abuse are potentially painful and may lead to increased pain tolerance (Van Orden et al, 2010), which was validated in several studies, for example, Allbaugh et al (2017). Sachs‐Ericsson, Stanley, Sheffler, Selby, and Joiner (2017) state that the underlying mechanisms between violent (sexual and physical) and non‐violent (emotional) abuse may differ.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Most frequently investigated (Norman et al, 2012) and relevant for the analyses presented here are sexual, physical, and emotional abuse. Especially sexual and physical abuse are potentially painful and may lead to increased pain tolerance (Van Orden et al, 2010), which was validated in several studies, for example, Allbaugh et al (2017). Sachs‐Ericsson, Stanley, Sheffler, Selby, and Joiner (2017) state that the underlying mechanisms between violent (sexual and physical) and non‐violent (emotional) abuse may differ.…”
Section: Introductionmentioning
confidence: 97%
“…Emotional abuse may occur less painful and life threatening but does not have less serious effects on mental health (Schilling, Weidner, Schellong, Joraschky, & Pöhlmann, 2015). In contrast to the assumptions of Van Orden et al 2010, Allbaugh et al (2017) found emotional abuse to be connected to CS, which has also been shown in a recent study from our group (Schönfelder et al, 2019). In line with the above presented results, the meta-analysis of Liu et al (2017) found all kinds of abuse (strongest evidence for emotional abuse) to be associated with suicidal behavior.…”
mentioning
confidence: 95%
“…Since experiences of physical and sexual abuse can be (physically) painful and frightening, it is not surprising that they are also known to be related to CS (Smith, Monteith, Rozek, & Meuret, 2017; Van Orden et al., 2010; Van Orden, Witte, Gordon, Bender, & Joiner, 2008). Interestingly, studies have also found a relationship between emotional abuse and CS (Allbaugh et al., 2017; Schönfelder et al., 2019), even though that is, strictly speaking, not a physically painful experience. According to the WHO (2006, p. 18), emotional abuse includes: ‘the restriction of movement, patterns of belittling, blaming, threatening, frightening, discriminating against or ridiculing, and other non‐physical forms of rejection or hostile treatment’.…”
Section: Introductionmentioning
confidence: 99%
“…As this list of emotional abuse types includes some potentially fear‐inducing behaviours, it may help illuminate the direct relationship between emotional abuse and CS via the sub‐dimension fearlessness about pain and death . Several studies also have investigated the relationship between child abuse, the components of the IPTS (Allbaugh et al., 2017; Schönfelder et al., 2019; Smith et al., 2017), and suicidality (Allbaugh et al., 2017; Schönfelder et al., 2019, 2021) in mediation models. Since these four studies are fundamental for the present study, a brief introduction is in order.…”
Section: Introductionmentioning
confidence: 99%
“…relationship between the assurance of the maternal style and depression, but also the relationship between that perception of assurance and thoughts about suicide (Venta et al, 2014). Other family variables such as child abuse -emotional, accumulative and severe -have been associated with suicidal ideation and resilience through PB (Allbaugh et al, 2017;Puzia et al, 2014), while variables such as the perception of parental rejection have found this kind of association with both of Joiner's interpersonal constructs and suicide (Campos & Holden, 2015).…”
Section: Article In Pressmentioning
confidence: 99%